Interrogation of novel CDK2/9 inhibitor fadraciclib (CYC065) as a potential therapeutic approach for AML - Wittawat Chantkran; Ya-Ching Hsieh; Daniella Zheleva; Sheelagh Frame; Helen Wheadon; Mhairi Copland (Cell Death Discovery, 2021)
Abstract Over the last 50 years, there has been a steady improvement in the treatment outcome of acute myeloid leukemia (AML). However, median survival in the elderly is still poor due to intolerance to intensive chemotherapy and higher numbers of patients with adverse cytogenetics. Fadraciclib (CYC065), a novel cyclin-dependent kinase (CDK) 2/9 inhibitor, has preclinical efficacy in AML. In AML cell lines, myeloid cell leukemia 1 (MCL-1) was downregulated following treatment with fadraciclib, resulting in a rapid induction of apoptosis. In addition, RNA polymerase II (RNAPII)-driven transcription was suppressed, rendering a global gene suppression. Rapid induction of apoptosis was observed in primary AML cells after treatment with fadraciclib for 6–8 h. Twenty-four hours continuous treatment further increased efficacy of fadraciclib. Although preliminary results showed that AML cell lines harboring KMT2A rearrangement (KMT2A-r) are more sensitive to fadraciclib, we found that the drug can induce apoptosis and decrease MCL-1 expression in primary AML cells, regardless of KMT2A status. Importantly, the diversity of genetic mutations observed in primary AML patient samples was associated with variable response to fadraciclib, confirming the need for patient stratification to enable a more effective and personalized treatment approach. Synergistic activity was demonstrated when fadraciclib was combined with the BCL-2 inhibitor venetoclax, or the conventional chemotherapy agents, cytarabine, or azacitidine, with the combination of fadraciclib and azacitidine having the most favorable therapeutic window. In summary, these results highlight the potential of fadraciclib as a novel therapeutic approach for AML.